Muhammad Iqbal (1877-1938): my inspiration - Abdul Razak, Mohd Abbas (2022)
My journey into Iqbal’s philosophical world dates back to my high school days. As a young man, I was always on the go searching for something that could elevate my Islamic spirit. From those days to the present moment, I am a person who has a huge interest in topics like; human nature, God, and spirituality. During my teenage days, as a way to quench my thirst on such topics, I used to drop by secondhand bookshops in the city in which I was raised. Recommended by the elders of the shops I visited, I read Maududi (1903-1979), Maryam Jameelah (1934-2012), Hasan al-Banna (1906-1949), Ali Shariati (1933-1977), Muhammad Asad (1900-1992) and a few other famous Muslim scholars.